2018
DOI: 10.1177/0284185117752551
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an iterative model-based CT reconstruction algorithm by intra-patient comparison of standard and ultra-low-dose examinations

Abstract: Background The explosive growth of computer tomography (CT) has led to a growing public health concern about patient and population radiation dose. A recently introduced technique for dose reduction, which can be combined with tube-current modulation, over-beam reduction, and organ-specific dose reduction, is iterative reconstruction (IR). Purpose To evaluate the quality, at different radiation dose levels, of three reconstruction algorithms for diagnostics of patients with proven liver metastases under tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…) for the training step because we wanted to see if such observers can predict the performance in images with decreased image quality. Compared to the analytical FBP, iDose is an iterative reconstruction algorithm which reduces image noise …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) for the training step because we wanted to see if such observers can predict the performance in images with decreased image quality. Compared to the analytical FBP, iDose is an iterative reconstruction algorithm which reduces image noise …”
Section: Discussionmentioning
confidence: 99%
“…The models were trained with data reconstructed with iDose and evaluated on data reconstructed with FBP to ensure a realistic setup where a MO is used to evaluate a new modality or algorithm. FBP is expected to deliver images with more image noise and a decreased image quality compared to iterative iDose . This way, we wanted to ensure that the models can also detect lower image qualities, thus, algorithms with worse performance can be identified.…”
Section: Methodsmentioning
confidence: 99%
“…5,9 Many noise reduction methods based on image-based iterative reconstruction algorithms have been developed for CT imaging and recent studies demonstrated the feasibility of low-dose (LD) protocols beneficiating of comparable image quality and diagnostic performance. [10][11][12][13] Sinogram-Affirmed Iterative Reconstruction (SAFIRE, Siemens Healthcare, Erlangen, Germany) is a hybrid iterative reconstruction technique incorporating a raw data-based iterative reconstruction algorithm and an image space iteration algorithm. 14,15 Low-dose and ultra-low dose (ULD)-CTC have been demonstrated to be feasible to reduce radiation dose maintaining a comparable image quality when using iterative reconstruction technique.…”
Section: Introductionmentioning
confidence: 99%
“…Pickhardt et al were able to maintain a sensitivity of 79.3% for abdominal lesions with an MBIR algorithm while reducing the dose by an average of 74% (18). Noël et al showed a significantly better detection with MBIR than with HIR and FBP in 77.9% reduced dose CT images (32). Choi et al were able to maintain a sensitivity of 97.9% for liver lesions while reducing the dose by one-third with an MBIR algorithm (33).…”
Section: Discussionmentioning
confidence: 99%